Accuracy of Ultrasound in the Diagnosis of Acute Appendicitis and Correlation with Histopathology - Shrestha, Aimandu; Khadka, Hensan; Poudel, Baburam; Basnet, Ranga Bahadur; Basnet, Siv Bahadur (Nepalese Journal of Radiology, 2018)
Introduction: Acute appendicitis is a common surgical condition; yet its diagnosis can be elusive at times and missed diagnosis can lead to attendant complications of perforation and its sequelae. On the contrary, negative appendectomy subjects one to unnecessary surgery and its physiological and psychological consequences. Among the various available modalities of diagnosis of appendicitis, Ultrasonography(USG) is easily accessible, non invasive, less time consuming, low cost investigation no radiation hazards. So, USG is appropriate diagnostic modality in our country. Methods: This prospective observational study was carried out from January 2011 to June 2011, in the radiology department of Bir hospital. Total of 80 cases with clinical impression of acute appendicitis were enrolled. These patients underwent surgery for suspected acute appendicitis. Details of signs and symptoms, lab findings including Total Leukocyte count (TLC), Differential Leukocyte Count (DLC) and USG findings were recorded. Intra-operative and histopathology findings were also recorded. The findings were analyzed to assess accuracy of ultrasonography in acute appendicitis. Histopathological report was considered the goal standard. Results: A total of 93 cases clinically diagnosed as acute appendicitis were subjected for USG. Out of 93 cases, 80 cases underwent surgery. Among 80 cases, sonography showed acute appendicitis in 56 cases out of which 54 was proved by histopathology as well. However, ultrasonography was not able to detect appendicitis in 9 cases. The sensitivity and specificity of USG for acute appendicitis were 87.7% and 88.2% respectively. The positive and negative predictive values were 96.4% and 62.5% respectively. Overall negative appendectomy rate of 21.2% had been used a basis for decision making, the rate of error being 13.7%. Conclusion: Ultrasonography is a fairly accurate and safe modality in acute appendicitis. It can be useful in reducing negative appendectomy rate.